2011
DOI: 10.1111/j.1440-1746.2010.06559.x
|View full text |Cite
|
Sign up to set email alerts
|

Utility of contrast‐enhanced ultrasonography with Sonazoid in radiofrequency ablation for hepatocellular carcinoma

Abstract: CEUS with Sonazoid is useful for HCC detection in patients with a well-conserved liver function reservoir. The decrease in RFA session numbers indicated the utility of Sonazoid in RFA treatment of HCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
74
1
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(76 citation statements)
references
References 22 publications
0
74
1
1
Order By: Relevance
“…In such cases, observation with Sonazoid™ CEUS may be effective. In addition, compared with the historical controls that were in place prior to the availability of Sonazoid™, the number of RFA sessions per treatment is reported to have decreased (25). Therefore, the effectiveness of Sonazoid™ CEUS in RFA has been confirmed.…”
Section: Discussionmentioning
confidence: 80%
“…In such cases, observation with Sonazoid™ CEUS may be effective. In addition, compared with the historical controls that were in place prior to the availability of Sonazoid™, the number of RFA sessions per treatment is reported to have decreased (25). Therefore, the effectiveness of Sonazoid™ CEUS in RFA has been confirmed.…”
Section: Discussionmentioning
confidence: 80%
“…2,12 Along with fusion imaging, contrast-enhanced sonography is widely used for interventional procedures on focal hepatic lesions. [13][14][15] However, compared with the fusion imaging technique, contrast-enhanced sonography is very much an operator-dependent technique and requires additional cost. Moreover, contrast-enhanced sonography can be challenging in localizing multiple or deeply located tar- get lesions because the temporal window of the arterial phase is not long enough, and detecting signals occurring due to microbubbles is limited in deeply located lesions.…”
Section: Discussionmentioning
confidence: 99%
“…As second-generation contrast agents including SonoVue and Sonazoid have been developed, CEUS has emerged as a rescue method for RFA for inconspicuous small HCC on B-mode US. Several studies reported that CEUS using Sonazoid was very useful in RFA for small HCCs (15,25). In one study, the initial success rate was 94%, and there was no case with local tumor progression during follow-up (15).…”
Section: Discussionmentioning
confidence: 99%
“…There are some new techniques to overcome the limitation of B-mode US-guided RFA (22)(23)(24)(25)(26)(27)(28)(29). One of the new techniques is fusion imaging-guided RFA.…”
Section: Discussionmentioning
confidence: 99%